EFEKTIVITAS PERAWATAN UNIT BOILER: STUDI KASUS DI PT. BEURATA SUBUR PERSADA - Maidi Saputra; Redha Kurniawan; Al Munawir (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
A boiler is a tool used to produce steam that is used for various purposes in palm oil mills. In a boiler system, the readiness and conditioning of the equipment are considered to meet the planned production targets. Maintenance, in particular on a boiler unit, is something that must be considered and essential to implement. This study aims to get an overview of the maintenance of the boiler unit at PT. Beurata Subur Persada. This research uses several methods in getting the desired results, including descriptive data collection/field interviews, from the observation and interview process with PT. Beurata Subur Persada, the planning of the maintenance process by factory conditions, is planned maintenance. Keywords: Boiler, Palm oil mills, Maintenance, Planned maintenance, PT. Beurata Subur Persada